2022
DOI: 10.1126/scitranslmed.abo0686
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme K + CD8 T cells form a core population in inflamed human tissue

Abstract: T cell–derived pro-inflammatory cytokines are a major driver of rheumatoid arthritis (RA) pathogenesis. Although these cytokines have traditionally been attributed to CD4 T cells, we have found that CD8 T cells are notably abundant in synovium and make more interferon (IFN)–γ and nearly as much tumor necrosis factor (TNF) as their CD4 T cell counterparts. Furthermore, using unbiased high-dimensional single-cell RNA-seq and flow cytometric data, we found that the vast majority of synovial tissue and synovial fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
100
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 78 publications
16
100
0
Order By: Relevance
“…A recent study determined GzmK-expressing CD8 + T cells in human inflammatory diseases including lupus nephritis. The authors also showed a low cytotoxic potential of GzmK + CD8 + T cells and highlighted them as major cytokine producers 53 . Interestingly, we found a similar correlation in patients with ANCA-associated cGN, since the inflammatory cytokines IFNG and TNF were predominantly expressed by GZMK + CD8 + T EM/CM and not by GZMB + CD8 + T Eff .…”
Section: Discussionmentioning
confidence: 97%
“…A recent study determined GzmK-expressing CD8 + T cells in human inflammatory diseases including lupus nephritis. The authors also showed a low cytotoxic potential of GzmK + CD8 + T cells and highlighted them as major cytokine producers 53 . Interestingly, we found a similar correlation in patients with ANCA-associated cGN, since the inflammatory cytokines IFNG and TNF were predominantly expressed by GZMK + CD8 + T EM/CM and not by GZMB + CD8 + T Eff .…”
Section: Discussionmentioning
confidence: 97%
“…While GZB has been shown to be critical in the host response to pathogens such as Klebsiella pneumoniae , ectromelia virus and lymphocytic choriomeningitis virus ( Müllbacher et al, 1999 ; Zajac et al, 2003 ; García-Laorden et al, 2016 ), it has also been implicated in severe outcomes of SARS-CoV-2 infection ( Adam et al, 2021 ; Kuchroo et al, 2022 ) and as a mediator of dysfunctional wound healing ( Hiroyasu et al, 2021 ; Turner et al, 2021 ). Less is known regarding the function of GZK, although it appears to also exhibit cytolytic and immunomodulatory potential ( Bouwman et al, 2021 ) and recently has been described as a key marker of CD8 + T-cells and macrophages enriched in inflamed tissues ( Turner et al, 2019 ; Jonsson et al, 2022 ). Importantly, the expression of both GZB and GZK have been shown to increase with age ( Mogilenko et al, 2021 ; Zöphel et al, 2022 ), which for GZB, has been postulated as a driver of pathological inflammation (i.e., inflammaging) in older adults ( Turner et al, 2021 ; He et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GZK+ CD8 + T-cells in human blood were mostly found within the central memory and CD57-negative effector memory compartments, while GZB+ cells were CD57 + effector memory with an exhausted TEMRA phenotype ( Mogilenko et al, 2021 ). Jonsson and colleagues ( Jonsson et al, 2022 ) identified a similar CD8 + subset characterized by high GZK expression and low GZB expression that were enriched in inflamed tissues, but exhibited low cytotoxic potential. Importantly, in both studies these subsets appear to be distinct from canonical CD8 + populations that exhibit abundant levels of GZB when activated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CD4 + T cells, our data suggest that CD1c + cDC and Mo might be able to induce activation of cytotoxic CD107a + IFN-γ + CD8 + T cells. It has been recently described that activated granzyme K + CD8 + T cells in the inflamed synovium might contribute to RA pathology ( 64 ). However, further studies are required to determine whether CD8 + T cells activated in the presence of CD1c + cDC can specifically acquire the phenotypical and functional properties of this particular granzyme K + CD8 + T cell subset.…”
Section: Discussionmentioning
confidence: 99%